TEXTUAL AND CONTEXTUAL MEANINGS IN TRANSLATION - Brata, Frans I Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 17 (2010): September 2010, 2010)
The translation of English pronouns into Balinese may have different linguistic variations. I-you (tu-vous) dalam Braun 1988:7 may have their translations into icang-cai ‘ordinary’, tiang-ragane ‘middle’, titiang-iratu ‘humble-refined’. He/She may have their translations into ia ‘ordinary’, dane ‘middle’, ipun ‘humble’, ida ‘refined’. Attitude in the Appraisal Theory, as a part of Linguistic Functional Systemic, used to investigate the social stratification of the tenors and that may determine the forms of the linguistic variants of the pronouns. The difference of the linguistic variants are due to (1) Textual meanings which are due to the two different linguistic systems and cultures and (2) Contextual meanings which are due to the translator’s preference.